Study of Neutronic and Temperature Distribution During Enrichment Reduction for BN-350 Reactor (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This paper represents the neutronic and thermal-hydraulic calculations for the conversion of BN-350 from 27% to 7% enriched Uranium fuel elements. Mixed enrichment cores have been studied where low enrichment uranium (LEU) cores fresh fuel elements substitute gradually the high enrichment uranium (HEU) depleted fuel elements in the equilibrium core.    Thermal-hydraulic calculations have been carried out to determine changes in the characteristics of the converted reactor during steady-state conditions and transient response to a coolant flow loss.